Step
*
2
1
1
1
1
of Lemma
poss-maj-invariant
1. T : Type
2. eq : EqDecider(T)
3. x : T
4. ys : T List
5. y : T
6. n : ℕ
7. z : T
8. (count(eq z;ys) - count(λt.(¬b(eq z t));ys)) ≤ n
9. ∀y:T. ((¬↑(eq z y)) 
⇒ (n ≤ (count(λt.(¬b(eq y t));ys) - count(eq y;ys))))
10. y = z ∈ T
11. (count(eq z;ys @ [y]) - count(λt.(¬b(eq z t));ys @ [y])) ≤ (n + 1)
12. y@0 : T
13. ¬(y@0 = y ∈ T)
14. ¬↑(eq z y@0)
⊢ (n + 1) ≤ ((count(λt.(¬b(eq y@0 t));ys) + 1) - count(eq y@0;ys) + 0)
BY
{ (RenameVar `w' (-3)⋅ THEN ((InstHyp [⌜w⌝] (-6)⋅ THEN Auto') THEN RW assert_pushdownC 0 THEN Auto)⋅) }
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  x  :  T
4.  ys  :  T  List
5.  y  :  T
6.  n  :  \mBbbN{}
7.  z  :  T
8.  (count(eq  z;ys)  -  count(\mlambda{}t.(\mneg{}\msubb{}(eq  z  t));ys))  \mleq{}  n
9.  \mforall{}y:T.  ((\mneg{}\muparrow{}(eq  z  y))  {}\mRightarrow{}  (n  \mleq{}  (count(\mlambda{}t.(\mneg{}\msubb{}(eq  y  t));ys)  -  count(eq  y;ys))))
10.  y  =  z
11.  (count(eq  z;ys  @  [y])  -  count(\mlambda{}t.(\mneg{}\msubb{}(eq  z  t));ys  @  [y]))  \mleq{}  (n  +  1)
12.  y@0  :  T
13.  \mneg{}(y@0  =  y)
14.  \mneg{}\muparrow{}(eq  z  y@0)
\mvdash{}  (n  +  1)  \mleq{}  ((count(\mlambda{}t.(\mneg{}\msubb{}(eq  y@0  t));ys)  +  1)  -  count(eq  y@0;ys)  +  0)
By
Latex:
(RenameVar  `w'  (-3)\mcdot{}  THEN  ((InstHyp  [\mkleeneopen{}w\mkleeneclose{}]  (-6)\mcdot{}  THEN  Auto')  THEN  RW  assert\_pushdownC  0  THEN  Auto)\mcdot{})
Home
Index